Avaliação de carcaça e carne de fêmeas bovinas aberdeen Angus x Nelore, superprecoces, terminadas em confinamento - (:unkn) unknown (Universidade Estadual de Goiás, 2017)
The meat is a noble food, source of protein of excellent quality. The population in Brazil and in the World is growing continuously and the demand for food has increased every year. The breeding and production of beef cattle face challenges and seek alternatives of short cycle production, with zootechnical efficiency and also improve the economic indexes of the activity. In this work, bovine females aged 12 and 15 months from crossbreeding of the Aberdeen Angus and Nellore rats were evaluated, finishing in confinement in a period of 151 days. There was no significant difference in initial and final weights, despite the difference of three months in age. The performances in weight gain, carcass yield, carcass dimensions and sensorial, physical and chemical evaluations of the Longissimus dorsi muscle were evaluated. The daily gain values were 1.070 and 1.067 kg, and the carcass yield without fasting, of 53.95 and 52.98%, respectively for Treatments 1 and 2. The carcass weights produced served the market, reaching Above the minimum slaughterhouse minimum weight for females. This demonstrates that even young animals, precocious and with adequate food, produce carcass and meat that meet the market demand. There were no significant differences in most of the evaluated items, except for the carcass yield with and without fasting. These values can influence the technical and economic performance of the production system. In view of the obtained results we can conclude that it is feasible to reduce the production cycle of beef cattle, with the slaughter of super young bovine females, without prejudice to the quality of carcass and meat, as well as the profitability indexes
Keywords: Cruzamento de bovinos; Precocidade; Intensificação; Eficiência zootécnica; Produção de bovinos; Carcaças; Matadouro frigorífico; Aberdeen Angus; Nelore; Crossbreeding; Precocity; Intensification; Zootechnical efficiency; Carcass; CIENCIAS AGRARIAS::ZOOTECNIA